Population growth, human capital expenditures and economic growth a macroeconometric analysis - Orbeta, Aniceto C., Jr (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1992)
The paper presents an econometrically estimated model where economic and demographic variables are determined simultaneously. It is used to quantify the importance of human capital expenditures in socioeconomic and demographic development as well as analyze the effects of rapid population growth on human capital expenditures. The simulation results indicate that human capital expenditures are important determinants of economic development, have appreciable negative effects on both fertility and infant mortality, hence, have negligible net effects on population in human capital expenditures per capita which implies a deteriorating quality of human capital.